1998
DOI: 10.1109/84.661385
|View full text |Cite
|
Sign up to set email alerts
|

A high-T/sub c/ superconductor bolometer on a silicon nitride membrane

Abstract: In this paper, we describe the design, fabrication, and performance of a high-T c GdBa 2 Cu3O 70 superconductor bolometer positioned on a 2-2 2-mm 2 1-m-thick silicon nitride membrane. The bolometer structure has an effective area of 0.64 mm 2 and was grown on a specially developed silicon-onnitride (SON) layer. This layer was made by direct bonding of silicon nitride to silicon after chemical mechanical polishing. The operation temperature of the bolometer is 85 K. A thermal conductance G = 3:3 1 10 05 W/K wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…After exposure, it is developed using AZ 400 solution and etching window is open by wet etching using Buffered Oxide Etchant (BOE). The bulk silicon is selectively etched away fro m the backside using Deep RIE process to min imize the heat loss of thermal infrared detector [3]. For the backside dry etching, at least 10 Pm-thick AZ 9260 photoresist mask is needed to passivate the substrate from ion attack.…”
Section: Design and Fabricationmentioning
confidence: 99%
“…After exposure, it is developed using AZ 400 solution and etching window is open by wet etching using Buffered Oxide Etchant (BOE). The bulk silicon is selectively etched away fro m the backside using Deep RIE process to min imize the heat loss of thermal infrared detector [3]. For the backside dry etching, at least 10 Pm-thick AZ 9260 photoresist mask is needed to passivate the substrate from ion attack.…”
Section: Design and Fabricationmentioning
confidence: 99%
“…To obtain this layer a new bond-and-etchback technique 14 involving a fusion bonding step between a silicon nitride layer (Si x N y ) and Si has been developed. [15][16][17] The 0.62 m low-stress Si x N y layer is grown by low pressure chemical vapor deposition. Prior to the bonding the surface roughness of the Si x N y is reduced by chemical mechanical polishing.…”
Section: Production Processmentioning
confidence: 99%
“…Moreover, it has been reported that the design, fabrication and performance of a high temperature GdBa 2 Cu 3 0 7-x , superconductor bolometer positioned on a thick silicon nitride membrane. The technological feasibility of this high-Tc superconductor transition edge bolometer investigated could satisfy the requirements of a Fabry-Perot (FP) based satellite instrument designed for remote sensing of atmospheric hydroxyl ion (Skchez et al, 1997). Furthermore, the SQUID readout has been already developed for bolometers such as Cold Electron Bolometer (CEB) (Kuzmin, 2006).…”
Section: Bolometer Applications Of High Temperature Superconductorsmentioning
confidence: 99%
“…The detector is kept at a temperature close to the middle of the superconducting transition, where the is maximum. The edge transition superconductive bolometers have been investigated in various studies (Skchez et al, 1997;Fardmanesh, 2004;Cámara Mayorgaa et al, 2006). Photo-mixing devices needed for hot electron bolometers, which have been verified with a superconductor-insulator-superconductor (SIS) mixer, have tremendous potential for various applications such as radio astronomy, terahertz imaging, high-resolution www.intechopen.com spectroscopy, medicine, security, and defense (Cámara Mayorgaa et al, 2006).…”
Section: Bolometer Applications Of High Temperature Superconductorsmentioning
confidence: 99%